Natural history of gastroesophageal reflux in infancy: new data from a prospective cohort - Marlène Curien-Chotard; Prévost Jantchou (BMC, 2020)
Abstract Background Gastroesophageal reflux (GER) is common in infants. Gastroesophageal reflux disease (GERD) is defined as GER leading to troublesome symptoms that affect daily functioning and/or complications. This study is aimed at determining the prevalence and progression of GER and GERD in a cohort of healthy term infants from birth to 12 months old. Methods We conducted a prospective cohort study including all full-term living neonates born at Besançon Teaching Hospital, France. Parents completed a clinical report form and the Infant Gastroesophageal Reflux Questionnaire-Revised (I-GERQ-R) at 1, 3, 6, 10, and 12 months of age. GER was defined as score ≥ 1 to the first question with I-GERQ-R score < 16, and GERD as score ≥ 1 to the first question with I-GERQ-R score ≥ 16. Regurgitation was based on the answer to the first question of the I-GERQ-R as anything coming out of the mouth daily. Results 157/347 births were included (83 boys). The prevalence of regurgitation at least once a day was 45.7% overall. In total: 72, 69, 56, 18, and 13% of infants regurgitated at least once a day at 1, 3, 6, 10, and 12 months of age, respectively. Physiological GER affected 53, 59, 51, 16, and 12% of infants; GERD, 19, 9, 5, 2, and 2%, respectively. Two risk factors were identified: family history of GER and exposure to passive smoking. Treatment included dietary modification (14%) and pharmacotherapy (5%). Conclusion Physiological GER peaked at 3 months, GERD at 1 month. Most cases resolved on their own. GER and GERD are very common in the infant's population and parents should be reassured/educated regarding symptoms, warning signs, and generally favorable prognosis. I-GERQ-R is useful to the clinical screening and follow up for GER and GERD.